Consecutive Rosochatius Deformations of the Garnier System and the Hénon-Heiles System - Baoqiang Xia; Ruguang Zhou (Abstract and Applied Analysis)
An algorithm of constructing infinitely many symplectic realizations of generalized sl(2) Gaudin magnet is proposed. Based on this algorithm, the consecutive Rosochatius deformations of integrable Hamiltonian systems are presented. As examples, the consecutive Rosochatius deformations of the Garnier system and the Hénon-Heiles system as well as their Lax representations, are obtained.